Litter Production, Decomposition, and Nutrient Release in Silver Fir (Abies pindrow) and Spruce (Picea smithiana) Forests of Northwest Himalayas - Singh, Ombir; Panwar, V. P.; Wani, Akhlaq Amin (Indian Forester, 2021)
Temperate forests of silver fir and spruce in western Himalayas meet high turnover of litter fall of 10393.97 Â± 488.43 kg/ha/y and 9708.17 Â± 1341.07 kg/ha/y, respectively. The decomposition rates (decay constant - k) are also very low (0.221 to 0.294) in both the species. Accordingly, a time period of 10 to 13 years is required for decomposing 95 per cent of total litter in these forests. Low concentration of N, P and K nutrients were observed in the month of April in which maximum needle fall was recorded in both the species. Nearly 35 per cent and 38 per cent of the nutrients may be withdrawn from the needles before leaf fall in silver fir and spruce, respectively. The mobility of different nutrients from decomposing needle litter is found as: K > Mg > P > N > Ca and K > Ca > N > P > Mg for silver fir and spruce, respectively. The annual nutrient return was observed as: Ca > N > K > Mg > Pin both these temperate coniferous species